Overton's Rule Helps To Estimate the Penetration of Anti-Infectives into Patients' Cerebrospinal Fluid - Djukic, Marija (American Society for Microbiology, 2012)
In 1900, Ernst Overton found that the entry of anilin dyes through the cell membranes of living cells depended on the lipophilicity of the dyes. The brain is surrounded by barriers consisting of lipid layers that possess several inward and outward active transport systems. In the absence of meningeal inflammation, the cerebrospinal fluid (CSF) penetration of anti-infectives in humans estimated by the ratio of the area under the concentration-time curve (AUC) in CSF (AUC(CSF)) to that in serum (AUC(CSF)/AUC(S)) correlated positively with the lipid-water partition coefficient at pH 7.0 (log D) (Spearman's rank correlation coefficient r(S) = 0.40; P = 0.01) and negatively with the molecular mass (MM) (r(S) = −0.33; P = 0.04). The ratio of AUC(CSF) to the AUC of the fraction in serum that was not bound (AUC(CSF)/AUC(S,free)) strongly correlated with log D (r(S) = 0.67; P < 0.0001). In the presence of meningeal inflammation, AUC(CSF)/AUC(S) also correlated positively with log D (r(S) = 0.46; P = 0.002) and negatively with the MM (r(S) = −0.37; P = 0.01). The correlation of AUC(CSF)/AUC(S,free) with log D (r(S) = 0.66; P < 0.0001) was as strong as in the absence of meningeal inflammation. Despite these clear correlations, Overton's rule was able to explain only part of the differences in CSF penetration of the individual compounds. The site of CSF withdrawal (lumbar versus ventricular CSF), age of the patients, underlying diseases, active transport, and alterations in the pharmacokinetics by comedications also appeared to strongly influence the CSF penetration of the drugs studied.